STABILITY INDICATING HPTLC METHOD DEVELOPMENT AND VALIDATION FOR COMBINED DOSAGE FORM OF TOLPERISONE HYDROCHLORIDE AND DICLOFENAC SODIUM - Bavaliya, Paresh; Kalkani, Vijay; Kashyap, Raval (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
A simple HPTLC method has been developed and subsequently validated for tabletdosage form. The method employed TLC aluminum plates precoated with silica gel60F254 as the stationary phase. The solvent system consist of Methanol: Toluene:Ethyl Acetate (2.5:7:0.5 v/v/v) and saturation time was 25 min.This system was foundto give compact spots for diclofenac sodium (Rf =0.7±) and tolperisone hydrochloride(Rf 0.5).Analysis of tolperisone hydrochloride, diclofenac sodium was carried out at275nm. Linearity of diclofenac sodium and tolperisone hydrochloride was found to bey = 5.3727x + 4514.2, R2=0.998, y = 9.376x + 2635.6, R2=0.995 respectively inconcentration range of 300-1500 µg/bandand 100-300 µg/band. %Assay oftolperisone hydrochloride and diclofenac sodium was found to be 99.16%w/v and99.60 %w/v.Results of all other experiments for method validation were found withinthe specified criteria of ICH guideline.